Moneyball in the Turkish Football League revisited: Anomalies in Galatasaray, Fenerbahce und Besiktas stock returns during COVID-19 incident - Ozdurak, C.; Ulusoy, V. (Journal of Economics Finance and Accounting, 2020)
Purpose - In this paper, we focus on the news impact analysis of the club stock returns. Galatasaray, Fenerbahçe and Besiktas stock prices skyrocketed in the last 3 months right after the suspension of leagued due to pandemic since they were not supported with the financial results of the clubs Methodology - We investigate the anomalies observed in the pandemic for three big football club stock returns by utilizing EGARCH models and News Impact Curves Findings- According to our EGARCH models we find that in Covid-19 period news impact persistency significantly increased for all three big club stock volatilities. Moreover, News Impact curves showed us in Covid-19 period the behavior of Fenerbahçe and Besiktas volatility changes. In the pandemic period after suspension of Turkish Football League bad news has more impact on Fenerbahçe and Besiktas stock volatility Conclusion- Since the leagues are suspended due to Covid-19 pandemic, and weak financial performances of all teams also do not support the stock price performances there is no fundamental explanation for this hike experienced in the last 3 months. This result confirms our first study conclusion which is sporting performances, excluding the unexpected wins, do not have any impact on the volatility of listed football clubs.